2019
DOI: 10.4274/tybd.galenos.2018.84856
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Education in Reducing Noise on Health Personnels’ Knowledge Level and Behavioral Change

Abstract: ÖZ Amaç: Gürültü özellikle preterm yenidoğanların ve sağlık çalışanlarının sağlığını olumsuz yönde etkilediği için azaltılması ve kontrol altına alınması gereken bir durumdur. Amerikan Pediatri Akademisi gürültü seviyesinin saatlik 45 dB'nin altında olması gerektiğini bildirmiştir. Ancak yapılan birçok çalışmalarda, istenilen düzeye ulaşılamadığı görülmektedir. Araştırma, yenidoğan yoğun bakım ünitesindeki gürültü düzeyini ve gürültü kontrolü için verilen eğitimin etkisini değerlendirmek amacıyla yapıldı. Gere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Thus, the study results show that the educational package that is teaching session and noise reduction protocol was effective in improving the awareness. The similar findings which were also evident in other study was done in Bagcilar Turkey where the findings revealed that the mean percentage was 67.35% in pre-test, 82.35% in post-test, and there was a significant difference between pretest and posttest at the level of (p<0.05) [6] .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Thus, the study results show that the educational package that is teaching session and noise reduction protocol was effective in improving the awareness. The similar findings which were also evident in other study was done in Bagcilar Turkey where the findings revealed that the mean percentage was 67.35% in pre-test, 82.35% in post-test, and there was a significant difference between pretest and posttest at the level of (p<0.05) [6] .…”
Section: Discussionsupporting
confidence: 88%
“…This shows that reminders among the staffs and exhibiting a poster on noise reduction strategies ensure adherence to acoustic environment. A similar another Study conducted in Bagcilar in Turkey also showed that observation of health personnel's behaviors in reducing noise in NICU was statistically significant at p<0.05 after the education even though some behaviors like not dragging things, using mobile phones in silent mode, remained the same 6 .After introduction of educational package there is reduction in the decibel of sound level in all the shift, that is in the morning 65 dB to 60 dB, in the afternoon 62 dB to 60 dB and in the night shift 64 dB to 61dB. This shows that the teaching session and exhibition of the poster on noise reduction strategies motivated the HCP to maintain the acoustic environment in NICU.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation